Metode penyelesaian untuk masalah Program goal linier fuzzy= Solution Methods for Fuzzy Linear Goal Programming Problems - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Goal programming is a mathematical programming technique that permits decision makers to set and prioritize multiple objectives. In real world problem, however, it is not very often that the coefficients and target values to be known precisely, so a decision maker may not be able to determine precisely the relative importance of the goal. Linear goal programming problems can be solved with either fuzzy linear goal programming formulation or standart linear goal programming models, by forming priority goal preemptive to obtain goal programming lexicographically approaching then solved by sequential algoritms. The value obtained from fuzzy linear goal programming formulation is almost similar with value resulted from standard linear goal programming models.